Literasi digital, technostress, dan adopsi teknologi Industri 4.0: Pendorong kinerja inovasi - Paul Jonathan; Angela Caroline; Yoke Pribadi Kornarius; Albertus Iwan Hendarta; Agus Gunawan (Jurnal Manajemen Maranatha, 2025)
Sophisticated technologies, including IoT, AI, Big Data, and robotics, are enabling Industry 4.0 to transform how products are created, and services are delivered, making processes far more efficient. This profound digital shift is notably impacting the healthcare sector, driving its adoption and growing dependence on technology to elevate service quality. One key factor in technology adoption in this sector is the digital literacy of healthcare professionals, which includes their ability to operate and utilize technology. However, technological development also brings new challenges, such as technostress, which is the pressure caused by rapid technological advancements. This study focuses on examining the effect of digital literacy and technostress on organizational innovation performance within the healthcare sector, where Industry 4.0 technology adoption acts as a mediating variable. The study involves 216 healthcare professionals in Bandung City, and the analysis was employed using Structural Equation Modeling (SEM-PLS). The study reveals that digital literacy and technostress significantly promote Industry 4.0 technology adoption. This adoption then acts as a catalyst for enhancing organizational innovation performance. The higher the digital literacy, the better the technology adoption rate, which supports the creation of innovation within organizations. Technostress, although adding pressure, can encourage individuals to adapt more quickly to new technologies, accelerating innovation. This study emphasizes the importance of high digital literacy and proper technostress management in driving technology adoption and enhancing innovation performance, particularly in the healthcare sector.